Role of Gender in the Prevalence of Myopia among Polish Schoolchildren - Maciej Czepita; Damian Czepita; Krzysztof Safranow (Journal of Ophthalmology)
Purpose. The aim of the paper was to study the role of gender in the progression of myopia among Polish schoolchildren. Materials and Methods. 4875 children from elementary schools and high schools were examined (2470 boys, aged 6–16 years, mean age 11.0, SD = 2.6 and 2405 girls, aged 6–16 years, mean age 11.1, SD = 2.6). The examined students were Caucasian and resided in and around Szczecin, Poland. The examination included retinoscopy under cycloplegia. The refractive error readings were reported as spherical equivalent (SE). Myopia was defined as SE of at least −0.5 D. Data analysis was performed using the Mann–Whitney U test and 2-sided Fisher’s exact test. p values of less than 0.05 were considered statistically significant. Results. It was found that the SE among Polish boys is similar to the SE among Polish girls before the age of 9 years. However, in older children, lower SE values and higher prevalence of myopia were found among girls than boys, both at 9–13 years range (0.45 ± 1.05 vs 0.55 ± 1.23 D, p=0.047 and 8.30% vs 5.71%, p=0.015, respectively) and at 13–16 years range (0.32 ± 1.14 vs 0.54 ± 1.08 D,  p=0.0093 and 10.37% vs 5.96%, p=0.0050), respectively. Conclusions. Gender is associated with the prevalence of myopia among Polish schoolchildren ranging from 9 to 16 years of age.